RESILIENCE OF ADULTS WITH HIGH-FUNCTIONING AUTISM (HFA) IN SITUATION OF STRESS AND FORCED ISOLATION DUE TO THE COVID-19 - Kuznetsova, L.V.; Kudyukina , A.P. (Modern Psychology, 2021)
In this research presented a comparative analysis indicator of resilience in respondents with autistic traits and neurotypical people. The study involved 40 respondents in every groups. Some new data have been received concerning the influence of Covid-19 pandemic on the indicators of resilience among adults HFA and adults without autistic traits; significant differences between these two groups have been discovered as for as the general level of resilience is concerned and the indicators of its components. Besides, some contribution has been made to the notion of the difference between coping-strategies and psychological defense mechanisms inherent to these groups of adults. The results of the research may be used to elaborate the methods of psychological support of people with autism spectrum disorders as well as to provide a basis for further studies of the pandemic influence on different groups of population including most vulnerable categories.
Keywords: resilience; indicators of resilience; high-functioning autism; Covid-19 pandemic; forced isolation